Brazilian foreign policy on Twitter: digital expression of attitudes in the early months of Bolsonaro\'s administration - Mello, Anna Carolina Raposo de (2019)
This work addresses the impact of social media interactions in Brazilian foreign policy attitudes, as these digital platforms appear to be not only open floors for spontaneous manifestations of opinion, but also important sources of information. Recent research has attested to the growing relevance of social media to the political universe, influencing electoral disputes and mobilizing citizens\' approval or rejection of policies. Still, public opinion studies about Brazilian foreign policy have yet to include digital networks in this specific field. Through Twitter monitoring under a theme-oriented frame of reference, this study has verified the presence of a bulky debate about Brazil\'s foreign affairs in the social platform, from April to June 2019. Focusing primarily on a description of this debate and the ways in which foreign policy issues were presented, we were able to identify a significant amount of foreign policy-related interactions, as well as the expression of attitudes in original tweets and other forms of engagement. These discussions mobilized a large community of Twitter users, who often expressed their foreign policy attitudes in connection with domestic politics, and according to the side they took in a polarized political environment. The most engaging content was frequently propelled by political figures and the media, reflecting the traditional public opinion formation dynamics between elites and the uninformed public. Outsiders and Internet influencers who did not belong to the so-called foreign policy community also played an important role in driving the conversation - which suggested the emergence of a new kind of digital \"elite\" informing Brazilian foreign policy mass attitudes. The foreign policy attitudes expressed on Twitter during this period came across as conditioned to political ideology and domestic stances online, in a seemingly heuristic shortcut: foreign policy stances propagated by leaders on each side of the political spectrum appeared to be appropriated by their respective supporters, in consistence with the theoretical assumption that in the face of an informational disadvantage, people use cognitive shortcuts to form their opinion. Our findings raise questions about the possible effects of online discussion: they acknowledge the need to further investigate whether the digital debate might have increased the salience of foreign policy issues in the national public debate, and whether foreign policy attitudes might have been instrumentalized in a context of strong polarization of domestic politics, such as the early months of Jair Bolsonaro\'s administration.